The use of discovery awareness in intellectual disability services: examining a European approach to challenging behaviour in a UK setting - Webb, Joseph Charles (2017)
A series of abuse scandals in recent years have stimulated debate regarding appropriate ways to care for people with intellectual disabilities and challenging behaviour, with policy emphasising the need to move beyond reactive and aversive approaches. This thesis presents a qualitative study of the use of Discovery Awareness; a non-aversive video-analysis based approach to challenging behaviour which aims to improve relational aspects of care. Fieldwork was undertaken over a 10 month period in two Assessment and Treatment Units on a single site in the UK. During this period, 7 Discovery Awareness sessions were filmed and 12 interviews were conducted with staff who had experience of attending DA sessions. The filmed DA sessions were analysed using Conversation Analysis (CA) whilst the interview data explored staff accounts and perceptions of using DA in practice. The findings demonstrate that method integrity is an interactionally achieved phenomenon accomplished by the chairperson establishing interactional frameworks, shaping the conditional relevance of turns in line with the aims of the session, and through signalling transgressions in situ. There was no one interactional rule that applied to the whole DA session, making participant transgressions probable. Stance and interpretation were central actions related to video analysis in the session. Participants in DA utilised vague language to reduce the ‘degree of liability’ that a speaker may face. Participants also employed experiential formulations when interpreting the patients’ behaviour. This both minimises the basis for disagreement and enables participants to bring to the surface tacit dimensions of knowledge regarding the patient. These skills may be valuable in care environments, where staff have to make decisions based on signs interpreted from patients in the moment. The conversation analytic work also uncovered the prevalent use of ‘imagined constructed inner dialogue’, in which staff members talk as the patients’ inner voice. This formulation was used to perform a variety of actions such as evidencing participants’ stances, gist formulating the turn of another speaker, and to imagine alternative courses of events from the patient’s point of view. The use of imagined constructed inner dialogue also enabled speakers to give voice to non-aligning turns which offer alternative assessments without the need for prefacing non-alignment and minimising disagreement commonly found in every day conversations. Whilst imagined constituted dialogue fulfils an epistemic function, it also enabled participants to fulfil one of the remits of a DA session; to try to see the world from the patient’s point of view. By speaking as the patient, staff take an empathetic stance and affiliate with the patient’s imagined experience whilst keeping the patient’s voice central, and debatable, in the sessions. The interview findings suggest that DA is perceived as a valuable tool in helping staff reflect on the behaviour and personhood of the patient, as well as their own role in interactions with the patient. Whilst a variety of positive outcomes were reported, there was no consensus about how or whether these factors resulted in a reduction in challenging behaviour. However DA was perceived as having a beneficial effect on the culture of the units and in promoting recognition of personal and collective skills relating to understanding and exploring the patients’ behaviour. Possible impediments to implementation were also identified through analysis of the sessions, staff interviews, and through a literature review focusing on the factors which promote or impede the use of methods in ID practice. The findings contribute to existing conversation analytic work on studying intellectual disability services from an interactional perspective. They also build on work examining how methods are implemented interactionally. This has relevance for understanding how ID methods are implemented in real world situations, and for ID policy and practice.